Effect of Sleep Restriction during Pregnancy on Fetal Brain Programming and Neurocognitive Development of Offspring: A Review - Gulia, Kamalesh K. (Annals of the National Academy of Medical Sciences (India), 2023)
We spend one-third of our lives in sleep, yet the core function of it still remains an enigma due to underlying complex neural processing in this altered state of consciousness. Sleep requirement varies with phase of development. Neonates spent about 85% of their time in sleep, which is polyphasic in nature. Gradually, this pattern takes the shape of a monophasic sleep in adolescents and adults, with changing micro- and macroarchitecture in every phase. Deprivation of sleep in adults impairs learning and memory, and reduces theta coherence among hippocampus and amygdale during sleep. However, sleep loss during pregnancy can affect the ontogenetic development of networks for sleep–wakefulness and the cognitive development of offspring. Even in normal pregnancy, poor sleep quality, reduced rapid eye movement (REM) sleep, and sleep fragmentation are common observation during the last trimester of pregnancy. Delta power, a marker for the homeostatic drive for sleep, in the NREM sleep during the last trimester of pregnancy and postpartum is increased. However, further sleep loss during late pregnancy is a growing concern. Neonates that are born to the total sleep-restricted dams present significant alterations in their emotional development (symptoms of hyperactivity, increased risk-taking behavior during periadolescence) and immature sleep–wakefulness patterns. The REM sleep restriction during late pregnancy elicits depressionlike traits in neonates, which persist until middle age. For a healthy development of brain and body, thorough understanding of the dynamic nature of sleep in relation to age and state (pregnancy) is instrumental in preventing the above-mentioned conditions of prenatal origin. Although sleep is essential for an active brain (for work during day), it remains an underestimated phenomenon. This review highlights the importance of sleep during pregnancy for a healthy brain network programming in offspring.
Keywords: REM sleep restriction; total sleep restriction; hyperactivity; depression; sleep loss during pregnancy; cognition; human; rat; behavior